A novel homozygous HES7 splicing variant causing spondylocostal dysostosis 4: a case report - Lv, Shaoguang; Wu, Yuanyuan; Liu, Fang; Jiao, Baoquan (Frontiers in Pediatrics, 2023)
Background Spondylocostal dysostosis 4 (SCDO4) is characterized by short stature (mainly short trunk), dyspnea, brain meningocele, and spina bifida occulta, which is caused by homozygous or compound heterozygous HES7 (HES family bHLH transcription factor 7) variants. The incidence of SCDO4 remains unknown due to the extremely low number of cases. This study reveals a novel homozygous HES7 splicing variant causing SCDO4 and reviews all the previously reported HES7 variants and corresponding symptoms, providing a comprehensive overview of the phenotypes and genotypes of HES7 variants. Case presentation This case report focuses on a Chinese neonate who was first hospitalized for tachypnea, cleft palate, and short trunk. After a series of auxiliary examinations, the patient was also found to have deformities of vertebrae and rib, left hydronephrosis, and patent foramen ovale. He underwent surgery for congenital hydronephrosis at 5 months old and underwent cleft palate repair when he was 1 year old. After two and half years of follow-up, the boy developed normally. A novel homozygous HES7 splicing variant (c.226+1G>A, NM_001165967.2) was identified in the proband by whole-exome sequencing and verified by Sanger sequencing. The variant was inherited from both parents and minigene assays demonstrated that this variant resulted in the retention of intron3 in the HES7 transcript. Including this case, a total of six HES7 variants and 13 patients with SCDO4 have been reported. Conclusions Our findings expand the genotype-phenotype knowledge of SCDO4 and provide new evidence for genetic counseling.